Gangguan Fungsi Paru dan Faktor-faktor yang Mempengaruhinya pada Karyawan PT.Semen Tonasa Pangkep Sulawasi Selatan - Mengkidi, Dorce; Nurjazuli, Nurjazuli; Sulistiyani, Sulistiyani (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2006)
ABSTRACT Background : One of the negative effect of cement industy is air pollution by dust. Dust emitted from cement factory, during burning process and from transportation of material to the factory and out from the factory and it’s also from packaging process. This pollution can influence the environment and human health. Method : This research was aimed to measure employee lung function and influenced factors at PT. Semen Tonasa. It was an observation study with a cross sectional design that observed 91 samples from May until June 2006. Data was obtained by interview with respondent, measured of lung capacity, body weight and height, and also measured cement dust concentration packing area, rawmill, cruser, mine, kiln and cement mill. Data analysis to done used univariat, bivariat to used Chi Square test and multivariat to used Logistic Regretion with enter method. Results : The results was shown that dust from cement in packing area was 18,47mg/m3, raw mill 1,63mg/m3, lime stone cruser 14,98 mg/m3, mine 20,23mg/m3, kiln 4,56mg/m3, cement mill 5,98mg/m3. Measurement of PT.Semen Tonasa employee lung fungtion shown an average lung fungtion capacity of the respondent was 88,22% FEV1/FVC with standart deviation 12,174, lowest value 48% FEV1/FVC and highest value 100% FEV1/FVC. Chi Square result shown there is significant relationship between age (p value = 0,015; RP = 1,721; 95% CI = 1,130 – 2,621), work duration ( p value = 0,017; RP = 1,768; 95% CI = 1,108 – 2,821), personal protective equipment (p value = 0,010; RP = 0,572; 95% CI = 0,390 – 0,838) and smoking habit (p value = 0,046; OR = 2,764; 95%CI = 1,020 – 7,495) with lung function disorder (p<0,05), Logistic Regretion result shown personal protective equipment (p value = 0,012; OR = 3,289; 95%CI = 1,299 – 8,327) and smoking habit (p value = 0,046; OR = 2,764; 95%CI = 1,020 – 7,495) can influence lung function disorders at the same time. Conclusion : Therefore it is important for controlling the impact of airpolution by utilization of masker and smoking prohibition while working to decrease lung function disorder. Key words : cement industri, cement dust, lung function disorders